2021
DOI: 10.1177/00332941211027322
|View full text |Cite
|
Sign up to set email alerts
|

Female Narcissism: Assessment, Aetiology, and Behavioural Manifestations

Abstract: Despite putative gender differences in the expression of narcissism, prominent theories have virtually dismissed the role of females in the development and manifestation of narcissism. The contention that narcissism is a pathology of the self that may partly differ in males and females is further evident in the Diagnostic and Statistical Manual of Mental Disorders (DSM-5). The DSM-5 reports that up to 75% of those diagnosed with Narcissistic Personality Disorder (NPD) are men. Such figures suggest that the rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 124 publications
2
15
0
2
Order By: Relevance
“…However, this hypothesis requires further validation in both, clinical and non-clinical samples. In line with the conclusion of Green et al (36) that gender may play a key factor that partly determines specific psychopathological constellations, our findings regarding the prevalence of vulnerable narcissistic features among women shed light on the specifics of addiction treatment in women. From a clinical perspective, the question remains whether unified regimen treatments based on discipline and order may not further increase the feeling of inferiority and thus dependence on authority, rather than promoting the growth of healthy female self-confidence and independence.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…However, this hypothesis requires further validation in both, clinical and non-clinical samples. In line with the conclusion of Green et al (36) that gender may play a key factor that partly determines specific psychopathological constellations, our findings regarding the prevalence of vulnerable narcissistic features among women shed light on the specifics of addiction treatment in women. From a clinical perspective, the question remains whether unified regimen treatments based on discipline and order may not further increase the feeling of inferiority and thus dependence on authority, rather than promoting the growth of healthy female self-confidence and independence.…”
Section: Discussionsupporting
confidence: 90%
“…The issue of gender differences is also a current topic of pathological narcissism research. Green et al (36) in a recent review pointed out the shortcomings of the hitherto prevailing way of evaluating narcissistic pathology, which primarily focuses on grandiose aspects that closely resemble prevailing masculine norms. A gender imbalanced approach to the assessment of narcissistic psychopathology may thus lead to the fact that manifestations of pathological narcissism in women are underdiagnosed, which can be manifested by shyness, shame, hypersensitivity, and low self-esteem, i.e., components typical of the vulnerable narcissistic prototype, rather than the aggressive self-assertion typical of the grandiose prototype (5).…”
Section: Introductionmentioning
confidence: 99%
“…Although the observed gender differences found in this study are consistent with the current literature, with males scoring exclusively higher on narcissistic grandiosity than females [ 34 ], recent empirical work on gender differences in pathological narcissism suggests gender disparities in both narcissistic expression and behaviour (for a review, see [ 31 ]. Considering that recent work has also highlighted that gender differences may arise in the endorsement of items pertaining to pathological narcissism (i.e., the items contained within instruments measuring pathological narcissism may have different meaning for the two genders, and more generally reflecting the male gender expression than that of females and feminine qualities, [ 32 , 39 ], an equally-distributed sample across both genders as well as the inclusion of different measures of pathological narcissism would allow for a more statistically sound and clinically relevant investigation of potential gender differences. This was however beyond the scope of the current study.…”
Section: Discussionmentioning
confidence: 99%
“…Men tend to diagnosed with this disorder more than women. DSM-5 reported that up to 75% of patients were men (Green, MacLean, & Charles, 2021). Men are often rated in narcissistic disorder higher than women (Golomb, Fava, Abraham, & Rosenbaum, 1995).…”
Section: In Adulthoodmentioning
confidence: 99%